Kinetics and mechanism of intramolecular Carboxylic Acid participation in the hydrolysis of N-Methoxyphthalamic Acid - Ariffin, Azhar; Khan, M.N. (2003)
The rate of formation and disappearance of phthalic anhydride (PAn) intermediate in the aqueous cleavage of N-methoxyphthalamic acid (NMPA) under acidic pH was studied spectrophotometrically in mixed CH3CN-H2O solvents. The rate of formation of PAn from NMPA is almost independent of the change in acetonitrile content from 20 to 70% v/v in mixed aqueous solvents. The rate constants for the formation of PAn from NMPA are similar to10-fold smaller than the corresponding rate constants for the formation of PAn from o-carboxybenzohydroxamic acid (OCBA). These observations are ascribed to the consequence of the occurrence of slightly different mechanisms in these reactions.